INCREASING THE CAPACITY OF KOPASTI AS A CLEAN WATER MANAGEMENT FROM SOURCES IN PASIRJATI, UJUNGBERUNG DISTRICT, BANDUNG CITY - Nyi Raden Ruyani; Mira Rosana Gnagey; Ahtu Duriat; Ediyanto Ediyanto (LPM Universitas Pasundan, 2021)
The clean water crisis began to emerge recently in the city of Bandung, especially when the water supply did not meet the needs of the residents, resulting in turmoil. Not only users and the government, but also PDAM as a provider are in trouble. Itinerant traders are also experiencing difficulties because demand continues to soar, while water sources are limited. According to Geodesy Expert from the Bandung Institute of Technology, Heri Andreas, Bandung is already experiencing a clean water crisis and currently the condition is getting worse. Without the intervention of the Government and Regional Governments in managing access to clean water, it is certain that the fate of big cities will have the potential for social conflict due to access to clean water.Springs as one of the shared water sources require management that includes mutual understanding and rules, service management and continuous maintenance. Increasing the Capacity of Kopasti to Manage Clean Water from Springs in Pasirjati Village, Ujungberung District, Bandung City through socialization, training and facilitation is expected to provide solutions faced by partners, especially with regard to opening a common understanding of the need for conservation efforts, protection of springs and management of archive administration and facilitation of work facilities. .